2012
DOI: 10.1080/1059924x.2012.632339
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma and Exposure to Pesticides: A Canadian Case-Control Study

Abstract: The objective of this study was to investigate the putative associations of specific pesticides with multiple myeloma. A matched, population-based, case-control study was conducted among men residing in six Canadian provinces (Quebec, Ontario, Manitoba, Saskatchewan, Alberta, and British Columbia). Data were collected on 342 multiple myelome cases and 1506 age and province of residence matched controls. Data were collected by mailed questionnaires to capture demographic characteristics, antecedent medical hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 21 publications
5
39
0
Order By: Relevance
“…The publication is related to the trans-Canada NHL study reported initially by McDuffie et al (2001) wherein there was a common control group for the study of several lymphopoietic cancers. Pahwa et al (2012) was updated by Kachuri et al (2013) and we defer consideration to that more recent publication. Kachuri et al (2013) presented a reanalysis and extension of Pahwa et al (2012) in which they excluded 149 (of 1506) controls who did not have an age match with the MM cases.…”
Section: Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The publication is related to the trans-Canada NHL study reported initially by McDuffie et al (2001) wherein there was a common control group for the study of several lymphopoietic cancers. Pahwa et al (2012) was updated by Kachuri et al (2013) and we defer consideration to that more recent publication. Kachuri et al (2013) presented a reanalysis and extension of Pahwa et al (2012) in which they excluded 149 (of 1506) controls who did not have an age match with the MM cases.…”
Section: Studiesmentioning
confidence: 99%
“…Pahwa et al (2012) was updated by Kachuri et al (2013) and we defer consideration to that more recent publication. Kachuri et al (2013) presented a reanalysis and extension of Pahwa et al (2012) in which they excluded 149 (of 1506) controls who did not have an age match with the MM cases. Kachuri et al utilized unconditional logistic regression to estimate ORs and presented analyses including and excluding proxy respondents (15% of controls and 30% of cases) and adjusting for smoking, which was associated with MM.…”
Section: Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive associations between the fungicide captan (OR, 2.35; 95% CI, 1.11-3.27) and the insecticide carbaryl (OR, 1.89; 95% CI, 0.98-3.67) and multiple myeloma were observed in a recent Canadian populationbased case-control study conducted among men in 6 Canadian provinces (ie, Quebec, Ontario, Manitoba, Saskatchewan, Alberta, and British Columbia). 186 The study consisted of 342 multiple myeloma cases and 1506 controls. Recent data have shown that multiple myeloma is consistently preceded by monoclonal gammopathy of undetermined significance (MGUS).…”
mentioning
confidence: 99%